Local development organisations in Saharan regions of North Africa: Expanding horizons. (28th June 2022) - Hamamouche, Meriem Farah; Faysse, Nicolas; Kuper, Marcel; Lejars, Caroline; Errahj, Mostafa; Kadiri, Zakaria; Ben Aissa, Nadhira; Benmihoub, Ahmed
Abstract: Local development organisations are now widespread in rural regions of North Africa. In the past, these organisations were usually only involved in a few sector‐specific activities. This study investigated the activities of 24 local development organisations in the Saharan regions of Morocco, Algeria and Tunisia. The fields of action of these organisations have expanded in the past decade, thanks to their increased capacity to handle relations with other actors. They have become active in defining what development means at the local level, although public administrations do not yet acknowledge such a role.